Antioxidative Properties of Iberis amara Extracts in Biochemical Model Reactions - Schempp, Harald; Totha, Angela; Weiser, Dieter; Elstner, Erich F. (Arzneimittelforschung, 2003)
Gastro-intestinal disorders such as the non-ulcer dyspepsia and irritable bowel syndrome expatiate on/with inflammatory processes of the gastro-intestinal mucosa. Iberogast is used in treatment of such disorders. Iberis amara L. extract (IAE) is one of nine components of the drug. There is increasing evidence that mediators of inflammation processes in the stomach and intestine include reactive oxygen species (ROS), arising from several enzymic reactions characteristic for inflammatory events. In this study it was shown that Iberis amara extract (STW 6) has the potential for scavenging ROS, dependent on the individual test system. Biochemical model reactions relevant for the formation of ROS in vivo at inflammatory sites were used. Inhibition of the formation of ROS could be shown to be excellent in test systems known to preferentially produce reactive species (myeloperoxidase-generated HOCl, peroxynitrite) with high affinities to sulfurcontaining compounds, e.g. mustard oil glycosides such as glucoiberin. Furthermore ROS, generated during xanthine oxidase (XOD)-catalysed oxidation of xanthine into uric acid, were also efficiently decreased by IAE. However, an inhibition of XOD could be excluded, but chelation of metal ions (Fe, Cu) decreasing their redox-cycling activities seems to play a role. A major activity of IAE proved to represent inhibition of lipid peroxidation processes, shown as delay of the lag phase of the Cu(II)-induced LDL oxidation as well as protection of α-linolenic acid from peroxidation by singlet oxygen.
Keywords: Iberis amara extract, antioxidative potential; Iberogast®; LDL oxidation; Myeloperoxidase; Peroxynitrite; Superoxide